Design and evaluation of lornoxicam bilayered tablets for biphasic release - Songa Ambedkar Sunil; Meka Venkata Srikanth; Nali Sreenivasa Rao; Sakamuri Balaji; Kolapalli Venkata Ramana Murthy (Universidade de São Paulo, 2012)
The objective of the present investigation was to develop bilayered tablets of lornoxicam to achieve biphasic release pattern. A bilayered tablet, consisting of an immediate and controlled release layer, was prepared by direct compression technique. The controlled release effect was achieved by using various hydrophilic natural, semi synthetic and synthetic controlled release polymers such as xanthan gum, hydroxypropyl methylcellulose (HPMC) and polyethylene oxide (PEO) to modulate the release of the drug. The in vitro drug release profiles showed the biphasic release behavior in which the immediate release (IR) layer containing the lornoxicam was released within 15 minutes, whereas the controlled release (CR) layer controlled the drug release for up to 24 h. All the bilayered tablets formulated have followed the zero order release with non-Fickian diffusion controlled release mechanism after the initial burst release. FTIR studies revealed that there was no interaction between the drug and polymers used in the study. Statistical analysis (ANOVA) showed no significant difference in the cumulative amount of drug release after 15 min, but significant difference (p < 0.05) in the amount of drug released after 24 h from optimized formulations was observed. Based on the release kinetic parameters obtained, it can be concluded that xanthan gum polymer was suitable for providing a biphasic release of lornoxicam. O objetivo do presente trabalho foi desenvolver comprimidos bicamada de lornoxicam para atingir padrão de liberação bifásica. Preparou-se, por compressão direta, comprimido bicamada, consistindo de uma camada de liberação imediata e uma de liberação controlada. A liberação controlada foi obtida pelo uso de vários polímeros naturais hidrofílicos, semi-sintéticos e sintéticos, tais como goma xantana, hidroxipropilmetil celulose (HPMC) e óxido de polietileno (PEO) para modular a liberação do fármaco. Os perfis de liberação in vitro mostraram comportamento bifásico em que a camada de liberação imediata (IR) contendo lornoxicam foi liberada em 15 minutos, enquanto a camada de liberação controlada (CR) liberou o fármaco em mais de 24 horas, Todos os comprimidos bicamada formulados seguiram a liberação de ordem zero com mecanismo de liberação controlada por difusão não fickiana após a liberação inicial por erupção. Os estudos de FTIR revelaram que não há interação entre o fármaco e os polímeros utilizados no estudo. A análise estatística (ANOVA) não mostrou diferença significativa na quantidade acumulada de fármaco após 15 minutos de liberação, mas observou-se diferença significativa (p<0,05) na quantidade de fármaco liberado após 24 h nas formulações otimizadas. Com base nos parâmetros de cinética de liberação obtidos, pode-se concluir que a goma xantana foi adequada para se atingir liberação bifásica de lornoxicam.